2017
DOI: 10.3390/nu9010037
|View full text |Cite
|
Sign up to set email alerts
|

An Online Survey on Consumer Knowledge and Understanding of Added Sugars

Abstract: Evidence of an association between added sugars (AS) and the risk of obesity has triggered public health bodies to develop strategies enabling consumers to manage their AS intake. The World Health Organisation (WHO) has strongly recommended a reduction of free sugars to 10% of total dietary energy (TE) and conditionally recommended a reduction to 5% TE to achieve health benefits. Despite food labelling being a policy tool of choice in many countries, there is no consensus on the mandatory addition of AS to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 25 publications
11
83
1
Order By: Relevance
“…Limited awareness of the correct definition of added sugar among the participants was also observed. A similar finding was reported among population of developed countries, including Ireland [18]. Influence of the social media on the nutritional knowledge of young adults has been suggested previously [26]; however, true definition of added sugar can be difficult to be understood through the social media.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Limited awareness of the correct definition of added sugar among the participants was also observed. A similar finding was reported among population of developed countries, including Ireland [18]. Influence of the social media on the nutritional knowledge of young adults has been suggested previously [26]; however, true definition of added sugar can be difficult to be understood through the social media.…”
Section: Discussionsupporting
confidence: 81%
“…Limited knowledge of dietary sugar and sweetener classification on food labels (natural sugar, added sugar, and artificial sweetener) was evident in Ireland, as only 4% of the study sample were able to correctly classify 10 or more ingredients from a list that contained 13 items. The study also reported that only 35% of the study sample were aware of the added sugar recommendation made by the WHO [18]. Additionally, the price per calorie for foods that are high in added sugar is lower compared to the price per calorie for healthy food options [19].…”
Section: Introductionmentioning
confidence: 91%
“…Some added sugar (EFSA) (1% TE) was also derived from Sugar-other ingredients which are likely to be derived from hidden sugar ingredients such as isoglucose. These hidden ingredients can be challenging to identify as added sugar on food labels [24,33]. This reinforces the need for clear labelling of ingredients in foods alongside product reformulation programmes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in all age groups, "sugars, preserves, sweet spreads" contributed to 8%-12% of Sugar-pureed fruit intake, and, in children and teenagers, "sugar confectionary" contributed to 6%-10% of Sugar-fruit juice intake. Specific sugar components such as Sugar-honey can also add into free sugar intake through foods that can be seen as healthy or sugar free [24,25]. For example, across all age groups, "breakfast cereals" contributed to Sugar-honey intake (7%-14%), "yogurt, fromage frais, dairy desserts" (12%-25%) and "diet soft drinks" (8%-21%) contributed to the Sugar-pureed fruit intake, and "savoury sauces and condiments" contributed to 3%-6% of Sugar-fruit juice intake which indicates that honey is widely used in breakfast cereals, pureed fruit is used in "yogurt, fromage frais, dairy desserts" and "diet soft drinks", and fruit juice is used in "savoury sauces and condiments".…”
Section: Contribution Of Food Sources To Sugar Intakesmentioning
confidence: 99%
“…Popular strategies to reduce intake of sugars are cutting back on processed and pre‐packaged foods, as well as HFSS foods such as cakes, biscuits, sugar‐sweetened carbonated drinks and fruit juices, and use of nutrition labels (Tierney et al . 2017). However, consumers face challenges putting these strategies into practice including poor understanding of food labels, difficulty in classifying ingredients as free or added sugars and confusion around which types of sugars to reduce.…”
Section: Strategies For Achieving Sugar Reduction – Common Approachesmentioning
confidence: 99%